Examining conspiracy theory spillover in the health communication arena: factors that impact COVID-19 conspiratorial beliefs and health-related behaviors - Pjesivac, Ivanka; Klein, Leslie; Zhao, Wenqing; Lu, Xuerong; Jin, Yan (Frontiers in Communication, 2025)
This study examined the strength of different groups of individual-level variables in predicting conspiracy beliefs about Coronavirus disease (COVID-19) and related health behaviors by conducting a survey on a national online sample of U.S. adults. The results indicated that, among a wide range of individual-level variables, including psychopathological variables, cognitive variables, trust perceptions, trait emotions, health-related variables, and demographics, general belief in conspiracy theories (CTs) best predicted belief in specific COVID-19 CTs. In addition, our results showed that a stronger belief in COVID-19 CTs served as a significant predictor of engaging in less avoidance behavior. Furthermore, our results indicated that belief in general CTs does not directly lead to a change in avoidance behavior; the relationship is instead mediated by belief in COVID-19 CTs. Perceived severity of COVID-19 was the best predictor for proactive health behavior, whereas actual vaccination behavior was best predicted by confidence in COVID-19 vaccines. These results were interpreted using a framework that combines health communication theories with the concepts of path dependency and spillover effects in conspiratorial thinking.